Prevencija i liječenje mukozitisa u bolesnika sa zloćudnim hematološkim bolestima pregled područja i stav Hrvatske kooperativne grupe za hematološke bolesti (KROHEM) = Prevention and treatment of mucositis in patients suffering from malignant hematological diseases : an overview of the subject matter and the attitude of the Croatian cooperative group for hematologic diseases KROHEM - Popović, Nika; Mravak-Stipetić, Marinka; Lelas, Antonela; Pulanić, Dražen; Radić-Krišto, Delfa; Aurer, Igor; Valković, Toni (2021)
Mukozitis označava bolnu upalu i oštećenje sluznice usta i gastrointestinalnog trakta koja se javlja kao komplikacija kemoterapijskog i/ili radioterapijskog liječenja i tijekom transplantacije krvotvornih matičnih stanica u bolesnika oboljelih od zloćudnih hematoloških bolesti. Navedeno stanje uvelike utječe na kvalitetu života i ishode liječenja bolesnika. U ovom preglednom radu opisani su čimbenici rizika za pojavu mukozitisa, učestalost, klinička slika, mjere prevencije i liječenja mukozitisa u bolesnika sa zloćudnim hematološkim bolestima te je na temelju aktualne literature i važećih svjetskih smjernica iznesen pregled područja i stav Hrvatske kooperativne grupe za hematološke bolesti (KROHEM).
Mucositis is the painful inflammation with lesions of the mucous membranes of the mouth and the gastrointestinal tract that commonly arises as an adverse effect of high dose chemotherapy and/or radiotherapy and during hematopoietic stem cell transplantation in patients suffering from malignant hematological diseases. Mucositis affects the patients" quality of life and the outcome of treatment. This review article describes the risk factors, prevalence, clinical picture, prevention measures and treatment of mucositis in patients suffering from malignant hematological diseases, and contains an overview of the subject matter and the attitude of the Croatian Cooperative Group for Hematological Diseases KROHEM, in accordance with the current literature and valid global guidelines.
Bibliografija: 38 jed.
Sažetak ; Abstract.
Keywords: Mukozitis -- Hematološke bolesti -- Faktori rizika -- Kvaliteta života -- Prevalencija